PCA analysis of the nighttime anomaly in far-from-geomagnetic pole regions from VTEC GNSS data - Meza, Amalia Margarita (2015)
The Weddell Sea Anomaly (WSA) is defined when the nighttime plasma density is greater than the daytime density in the area near the Weddell Sea, more specifically in the region limited by 50° S-70°S in latitude and 225° E-315° E in longitude. A similar ionospheric anomaly is also observed near the Okhotsk Sea in the northern hemisphere, and such a feature was named as Okhotsk Sea Anomaly (OSA). The objective of this work is to infer possible physical causes of the WSA and OSA phenomena. To that end, we applied the principal component analysis (PCA) technique to the vertical total electron content (VTEC) from global International GNSS Service (IGS) in order to analyze the temporal and spatial variations of the ionosphere during noon and night in far-from-magnetic pole regions, during a 3-year period at high (2000-2002) and low (2006-2008) solar activity conditions. The first mode of PCA applied on VTEC scattering represents on average the 93 % of the total VTEC variability. Thus, the PCA expansions up to mode 1 resulted enough to show WSA and OSA during summer solstices in both solar activity conditions, as well as WSA during spring equinox during low solar activity. Besides, the analysis of the temporal variations of these first modes should provide the interpretation of a probable physical explanation to the observed anomalies. We conclude that the main contributors to the anomalies should be a combination of the same physical mechanisms that explain annual variation and semiannual anomaly in that regions located far from the magnetic poles.